RESPON FISIOLOGIS AYAM JANTAN TIPE MEDIUM DI KANDANG PANGGUNG DENGAN KEPADATAN BERBEDA - Tri Yunike; Sri Suharyati; Khaira Nova (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This study was conducted from February to March 2011, in the chicken coop belonging to PT.Rama Jaya Lampung in the village of Jati Baru, Tanjung Bintang subdistrict , South Lampungregency. The chicken is a rooster who used a medium type strain MB 502. This study used acompletely randomized design (CRD), consisting of three treatments, with as many replicationssix times, namely R1: 16 tail cage density m-2, R2: 19 tail cage density m-2, and R3: density tailenclosure 22 m-2. The resulting data were analyzed with analysis of variance ,at the 5%significance level.Data obtained from the results of this study indicate that the density of the cage 16, 19, and 22 tailm-2 had no significant effect (P>0,05) on respiratory rate, rectal temperature and the temperature ofthe medium shank type rooster. The average value of respiratory frequency rooster different typesof medium density is the density of the tail enclosure 16 m-2 (R1) of 52,67 beats/min, the tail cagedensity 19 m-2 (R2) of 52,60 times/min, and cage density tail 22 m-2 (R3) of 53,80 beats/min, theaverage value of rectal temperature rooster type of medium in a different cage density is thedensity of the tail enclosure 16 m-2 (R1) of 39,85ºC, the tail cage density 19 m-2 (R2) of 39,85ºC,and the density of the tail enclosure 22 m-2 (R3) of 39,86ºC, and the average value of thetemperature of the medium shank type rooster coop at different densities, namely the tail cagedensity 16 m-2 (R1) of 37,69ºC, the density tail enclosure 19 m-2 (R2) of 37,67ºC, and the tail cagedensity 22 m-2 (R3) at 37,67ºC.